EVITALISASI PEMBELAJARAN AQIDAH AKHLAK: PENGEMBANGAN KEPRIBADIAN PESERTA DIDIK - Nurdiansyah, Nana Meily (JIEGC Journal of Islamic Education Guidance and Counselling, 2021)
Madrasas are formal institutions under the command of the Ministry of Religion of the Republic of Indonesia and Foundations as institutional stakeholders in madrasas which are organized by the community, the progress of civilization in the world of education rests with educators in each madrasa. Now education is faced with the world of Industry 4.0. MTs Hudaatul Umam revitalizes the learning of moral aqeedah in developing the personality of students as a collaborative form to revive innovation-based learning as the progress of a nation. The purpose of this study was to find out and analyze the revitalization of learning at MTs Hudaatul Umam. Sources of data obtained from the principal, teachers, and students. This research used a descriptive qualitative method (Field Research) with a sociological approach.